Exploring causes of bribery: a case study in a public organization in Malaysia - Sathappan, Malini; Omar, Zoharah; Arif Ismail, Ismi; Sathappan, Ramesh (Macrothink Institute, 2016)
Purpose: The purpose of the research paper is to explore and understand the causes of bribery among law enforcement officers in Malaysia. Methodology: Qualitative method was used in this research paper. Data collected using semi structured interview, documents and field observation. The research used non-random sampling among seven various rank officers. Furthermore it is an exploratory study as it explores causes of bribery among law enforcement officers in Selangor state. Findings: The findings derived four themes based on the cause of bribery namely (1) family, (2) public, (3) individual and (4) organization. Law enforcement officers believed bribery is a cause of officers being suspended and terminated from their job. Additionally a model has been developed on causes of bribery. Practical implications: Findings showed that practices of bribery among various level of officers who have to work together to address the issue of bribery in Malaysian law enforcement agency through formulated policies and strategies. Originality/value: This study may assist Malaysian enforcement agencies in identifying causes and overcoming bribery. It also provided a clear idea about how the cause of bribery can influence the behavior of an officer which can harm an organization.